BAS/BSCR7 Demonstration of gene expression within a thrombus: further regulation of the haemostatic response. Issue 17 (26th August 2010) - Wright, J R; Ellis, P; Langford, C; Watkins, N A; Ouwehand, W H; Goodall, A H
Abstract : Vascular injury and plaque rupture activate the haemostatic response, resulting in the formation of a thrombus comprising platelets, red cells and leucocytes, incorporated into a mesh of plasma proteins. Whether cells within the thrombus act simply as structural and secretory components, or have a more active role involving gene expression is unclear. To investigate this, thrombi were produced at 37°C in a Chandler loop, using re-calcified citrated blood from healthy donors (n=6). The thrombi were removed after 2, 4 and 6 h of rotational incubation, and homogenised to extract total RNA. Following in vitro transcription, samples were hybridised to Illumina WG6 beadchips, and data normalised using Illumina Beadstudio. Differences in gene expression were assessed using a Student t test, applying fdr2d correction to eliminate false positives (R Bioconductor). Genes which demonstrated significant (>twofold) time-dependent increases included genes encoding proteins involved in chemotaxis (IL8, CCL2, CXCL1, CXCL2, CXCR4), cell adhesion (ITGAV, ITGA5, ITGB1, ALCAM), regulation of coagulation (THBD, PLAU, SERPINE1, ANXA5), wound healing (TGM2, ENDG, SPP1, LAMB3, PTGS2, TNFAIP6) and regulatory transcription factors (FOS, BMP6, IRAK2, KLRG1, PPARG). Whereas initiation of thrombosis is driven by plasma proteins and facilitated by the platelet surface, this study provides evidence that thrombus resolution may be driven by changes in gene expression within the thrombus that regulate the haemostatic response, thrombus growth and facilitate wound healing. This finding could have implications for individuals at risk of plaque rupture, where variation in gene expression may affect not just the formation of an occlusive thrombus but also the rate of resolution.